Preparation of biodiesel synthesis from cooked oil waste catalyzed by sodium hydrate and microwave - Nguyen, Vũ Lân; Hsiao, Ming Chien (Journal of Technical Education Science, 2015)
In this paper, cooked oil waste with high acid value was used for transesterification reac- tion to produce biodiesel. The reaction was enhanced simultaneously by NaOH catalyst and microwave power. Results shown that under the effect of the microwave, the conversion rate reached to an optimal value of 98.1% when reaction conditions were: methanol:oil ratio 12:1; weight concentration of NaOH catalyst 0.8%; reaction system temperature 65oC; reaction pe- riod 02 minutes and microwave power 600W. This was a significantly high conversion yield although it was obtained within only 02 minutes. Also, the yield was high enough to satisfy the required conversion rate of 96.5% (National Taiwan standard, CNS-15072). Besides, the reaction rate constant increased from 0.635[min-1] to 2.369[min-1] when reaction temperature increased from 55oC to 65oC, respectively. The calculated activation energy for the transesteri- fication reaction was 123.14kJ/mol.